2015
DOI: 10.1016/j.micres.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Methods of isolation and purification of outer membrane vesicles from gram-negative bacteria

Abstract: Outer membrane vesicles secreted by gram-negative bacteria play an important role in bacterial physiology as well as in virulence and host-pathogen interaction. Isolated vesicles of some bacteria have also been studied for their immunomodulatory potential in the vaccine development. However, the production of vesicles in sufficient amount, purity and reproducibility remains a critical challenge for subsequent analyses in most bacteria. In the present review methods of production, isolation, purification and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
221
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(234 citation statements)
references
References 78 publications
0
221
0
Order By: Relevance
“…Consequently, both membranes have to remain functional even under variable conditions. The bestinvestigated mechanism that involves changes in the outer membrane of Gram-negative bacteria is the formation of outer membrane vesicles (OMVs) (Kulp & Kuehn, 2010;Klimentová & Stulík, 2015). The OMVs are released during all growth phases of the bacterial cultures (Kadurugamuwa & Beveridge, 1995;Manning & Kuehn, 2011), although their amount and composition may vary according to the growing conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, both membranes have to remain functional even under variable conditions. The bestinvestigated mechanism that involves changes in the outer membrane of Gram-negative bacteria is the formation of outer membrane vesicles (OMVs) (Kulp & Kuehn, 2010;Klimentová & Stulík, 2015). The OMVs are released during all growth phases of the bacterial cultures (Kadurugamuwa & Beveridge, 1995;Manning & Kuehn, 2011), although their amount and composition may vary according to the growing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies of OMV invariably showed that they are small spherical particles, from 50 to 250 nm, enclosed by a membrane bilayer, that contain phospholipids (PLs), LPSs, proteins and in some cases nucleic acids. They are also involved in the transport of metabolites, toxins, signalling molecules and other small molecules (Horstman & Kuehn, 2000Dutta et al, 2004;Keenan et al, 2008;Bomberger et al, 2009;Schertzer & Whiteley, 2012;Biller et al, 2014;Klimentová & Stulík, 2015). Furthermore, the formation of OMVs is a crucial part of the bacterial envelope stress response, protecting the bacteria from internal and external stressors (Manning & Kuehn, 2011;Baumgarten et al, 2012;MacDonald & Kuehn, 2012;Schwechheimer et al, 2013Schwechheimer et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Methods used for the isolation of the OMV and EV include ultracentrifugation and precipitation [2]. The isolation of OMV starts from culture supernatant after removal of cultured bacteria by centrifugation at 6,000 × g for 5 min.…”
Section: Isolation Purification and Quantification Of Omv And Evmentioning
confidence: 99%
“…OMVs are also reported to behave as secretion system for factors related to virulence and toxins inside a host, facilitate survival in the inter-species environmental competition, intra-and inter-species communication, secretion of proteins which are misfolded and aggregated (a novel stress response mechanism) etc. [2]. Both pathogenic and non-pathogenic species of Gram-negative bacteria are known to release vesicles [3][4][5][6], including Escherichia coli [7,8], Borrelia burgdorferi [9], Neisseria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, EVs/OMVs are purified via ultracentrifugation, density gradient fractionation, immunoaffinity, precipitation or ultrafiltration techniques [15]. Ultracentrifugation, which is utilized for both pelleting EV/OMV and density gradient fractionation, requires centrifugal forces of 100,000 × g or greater, necessitating access to expensive and specialized centrifugation equipment.…”
Section: Introductionmentioning
confidence: 99%